¿Por qué estudiar Sociología?: un análisis de los factores que intervienen en la elección de la Sociología como carrera universitaria en estudiantes de la PUCP - Huerta Gonzales, Edith (2021)
The following research aims to explore the main factors that influence the choice of career in university higher education. It focuses particularly on the case of young Sociology students at the Faculty of Social Sciences of Pontificia Universidad Católica del Perú (PUCP). It seeks to feed the corpus of research on the choice of professional career and contribute to the characterization of students and future sociologists in the country. The study proposes to use a theoretical framework that includes theory of rational choice, theory of social reproduction and gender perspective. The methodology used follows a mixed approach applied in a non-probabilistic sample. This combines a self-administered virtual anonymous survey by 43 of the students enrolled in the 2020-2 semester and qualitative interviews with a small group of these to deepen the responses about their educational trajectory and link with the specialty. The main results indicate that, in 76 % of Sociology students, the career they are currently studying was not their first option, but they started studying other professions. Additionally, it is noted that, in many cases, the decision to opt for this specialty is framed in an institutional environment, in which the influence of professors and courses related to the discipline of social sciences are relevant factors. Regarding the motives, the intrinsic value of the career prevails over its economic potential. In view of this, the relevance and importance of replicating this type of study in the rest of Peruvian universities that offer training in this specialty is foreseen.